Kompetensi Guru PAI dalam Menguasai Karakteristik Peserta Didik di SD Islam Ibnu Syam Kubang Putih Kabupaten Agam - Zahara, Rinda Mai; Junaidi, Junaidi; Deswalantri, Deswalantri; Alimir, Alimir (Faidatuna, 2024)
This research is motivated by the fact that teacherss must have competence in mastering the characteristics of student. Competence can also be interpreted as ability, in this case teachers must also have their own abilities, which are useful for achieving the hopes we aspire to in implementing education in general and the teaching and learning process in particular. In order for a teacher to have the ability, he needs to develop himself well because the theacher’s function is to develop, develop students abilities professionally and master the characteristics of students, The result of this research show that the factors that cause teachers to not master the characteristics of students consist of several factors, including moral-emotional, sociol-cultural, physical, intellectual and moral factors. The teacher has mastered the characteristics of student in terms of moral- emotional factors well but is not optimal because when the teacher explains the learning material there are some students who do not pat attention to the teacher in explaining the learning material. To achieve good moral-emotional character for students, teachers try to increase self-awareness related to their own moral and emotional values.